Calculating the frequency of composite plate and composite spherical shell with different boundary conditions - Adnan Yaseen, Aya; S. Alansari, Luay; Hussain Alnajem, Mohammed; S. Al-anssari, Qusay (International Journal of Engineering and Technology, 2018)
In this work, the Fourier-Ritz approach is used to calculate the natural non- dimensional frequency of composite plate and composite spherical shell with different arrangements of layers (cross and angle ply and symmetrical and anti-symmetrical layers) and different boundary conditions. The Fourier-Ritz approach is the modified Fourier series in connection with aÂ Â Ritz techniqueÂ Â to deduce the formulation based on the classical shallow shell theory. Additionally, the Finite Element method (FEM) (ANSYS Software Version 17.2) is used in this work for predicting the natural non- dimensional frequency of composite plate and composite spherical shell. The effect of (b/a) ratio on non- dimensional frequency of composite plate and composite spherical shell is studied for different layers arrangements when the boundary conditions are (CCCC) and (SSSS). The comparisons between the non- dimensional frequency results are made.